Blood Muramidase Activity in Colorectal Cancer - Cooper, E. H. (1974)
The serum muramidase levels were measured in 128 patients with primary or metastatic colorectal cancer, 166 tumour-free patients after resection of a colorectal cancer, and 172 controls. Muramidase levels over 10 μg/ml were detected in 30%-39% of the tumour-bearing patients, in 8·2% of the tumour free, and in only 1·7% of the controls (normal level 6·68 ± 1·42 μg/ml). Long-term follow up indicated that raised levels may occur as a transient phenomenon in recurrent or metastatic disease. The likely relation of abnormal serum muramidase activity and stimulation of the reticuloendothelial system is discussed.